Generation of three-dimensional meat-like tissue from stable pig epiblast stem cells - Gaoxiang Zhu; Dengfeng Gao; Linzi Li; Yixuan Yao; Yingjie Wang; Minglei Zhi; Jinying Zhang; Xinze Chen; Qianqian Zhu; Jie Gao; Tianzhi Chen; Xiaowei Zhang; et al. (Nature Communications, 2023)
Abstract Cultured meat production has emerged as a breakthrough technology for the global food industry with the potential to reduce challenges associated with environmental sustainability, global public health, animal welfare, and competition for food between humans and animals. The muscle stem cell lines currently used for cultured meat cannot be passaged in vitro for extended periods of time. Here, we develop a directional differentiation system of porcine pre-gastrulation epiblast stem cells (pgEpiSCs) with stable cellular features and achieve serum-free myogenic differentiation of the pgEpiSCs. We show that the pgEpiSCs-derived skeletal muscle progenitor cells and skeletal muscle fibers have typical muscle cell characteristics and display skeletal muscle transcriptional features during myogenic differentiation. Importantly, we establish a three-dimensional differentiation system for shaping cultured tissue by screening plant-based edible scaffolds of non-animal origin, followed by the generation of pgEpiSCs-derived cultured meat. These advances provide a technical approach for the development of cultured meat.